Update on the diagnosis and management of COVID-19 in pediatric patients - Carlotti, Ana Paula de Carvalho Panzeri (Clinics (Sao Paulo), 2020)
Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), became a pandemic in March 2020, affecting millions of people worldwide. However, COVID-19 in pediatric patients represents 1-5% of all cases, and the risk for developing severe disease and critical illness is much lower in children with COVID-19 than in adults. Multisystem inflammatory syndrome in children (MIS-C), a possible complication of COVID-19, has been described as a hyperinflammatory condition with multiorgan involvement similar to that in Kawasaki disease or toxic shock syndrome in children with evidence of SARS-CoV-2 infection. This review presents an update on the diagnostic methods for COVID-19, including reverse-transcriptase polymerase chain reaction (RT-PCR) tests, serology tests, and imaging, and summarizes the current recommendations for the management of the disease. Particular emphasis is placed on respiratory support, which includes noninvasive ventilation and invasive mechanical ventilation strategies according to lung compliance and pattern of lung injury. Pharmacological treatment, including pathogen-targeted drugs and host-directed therapies, has been addressed. The diagnostic criteria and management of MIS-C are also summarized.